Robin Hood - Ingle, Annie; D'Andrea, Domenick; Pyle, Howard, 1853-1911. (New York : Random House, 2005)
Robin Hood, Maid Marian, and the merry outlaws of Sherwood Forest repeatedly outwit the sheriff of Nottingham and befriend the poor.
Life in Sherwood Forest has never been livelier than with this selection of tales of the fun-loving outlaw and his merry men. A fast-moving adaptation of the classic adventure will delight older slow readers as well as kids reading on grade level.
RL:2.4.
007-009.
Keywords: Robin Hood -- (Legendary character) -- Legends; Robin Hood -- (Legendary character) -- Legends; Folklore -- England